The Evolving Relationship Between Corporate Governance and Corporate Strategy: A Comprehensive Literature Review - Seger Santoso; Dadang Irawan (Jurnal Pajak dan Analisis Ekonomi Syariah, 2025)
This qualitative literature review explores the evolving relationship between corporate governance and corporate strategy, focusing on recent insights and identifying future research directions. Drawing on a comprehensive analysis of studies from 2023–2024, the review highlights the pivotal role of governance mechanisms—such as board composition, accountability frameworks, and sustainability integration—in shaping strategic decision-making. Key findings reveal the increasing importance of diversity, long-term ownership structures, and adaptive governance practices in addressing global challenges. Furthermore, the study synthesizes the impacts of governance on strategic outcomes, emphasizing areas requiring further empirical exploration, such as the intersection of sustainability and innovation. This review contributes to the academic discourse by offering a consolidated perspective on governance-strategy dynamics while providing a roadmap for future research endeavors. Limitations and avenues for advancing the theoretical and practical understanding of this critical relationship are also discussed.